A history of Canadian literature - New, William H. (McGill-Queen's University Press, 2003)
New offers an unconventionally structured overview of Canadian literature, from Native American mythologies to contemporary texts. Publishers Weekly A History of Canadian Literature looks at the work of writers and the social and cultural contexts that helped shape their preoccupations and direct their choice of literary form. W.H. New explains how - from early records of oral tales to the writing strategies of the early twenty-first century - writer, reader, literature, and society are interrelated. New discusses both Aboriginal and European mythologies, looking at pre-Contact narratives and also at the way Contact experience altered hierarchies of literary value. He then considers representations of the "real," whether in documentary, fantasy, or satire; historical romance and the social construction of Nature and State; and ironic subversions of power, the politics of cultural form, and the relevance of the media to a representation of community standard and individual voice. New suggests some ways in which writers of the later twentieth century codified such issues as history, gender, ethnicity, and literary technique itself. In this second edition, he adds a lengthy chapter that considers how writers at the turn of the twenty-first century have reimagined their society and their roles within it, and an expanded chronology and bibliography. Some of these writers have spoken from and about various social margins (dealing with issues of race, status, ethnicity, and sexuality), some have sought emotional understanding through strategies of history and memory, some have addressed environmental concerns, and some have reconstructed the world by writing across genres and across different media. All genres are represented, with examples chosen primarily, but not exclusively, from anglophone and francophone texts. A chronology, plates, and a series of tables supplement the commentary.